ANALISIS TINGKAT KESESUAIAN ANTARA NILAI PEROLEHAN OBJEK PAJAK (NPOP) DENGAN NILAI PASAR DI DISTRIK MIMIKA BARU KABUPATEN MIMIKA PROVINSI PAPUA - , Darius Sabon Rain, Dr. Wahyu Widayat, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the congruity level between the reported AVTO and the actual market value in the region of New Mimika District, Mimika Regency of Papua Province. This study uses property market value data as primary data and AVTO data as secondary data. The method to determine sample uses cluster sampling method which means sampling is drawn by dividing the population into small clusters (village), and observations are made on clusters sample with proviso that the number of inter-cluster sample is proportional to the number of property sale and purchase transaction in the field of study. The analytical tool used in this study is assessment sales ratio. The results showed that AVTO determination was proportional or congruent with to the market value. Based on central tendency measurement, mean/median was 0.90 (values are in the range 0,90 to 1,10) so that it was proportional, while mean/weightedmean was 0,90 resulting a progressivity. Level of assessment test showed t-test (-5,978) was smaller than t-table (2,045). Thus it could be concluded that AVTO determination was relatively congruent with market value